Uso do canabidiol no tratamento de epilepsias refratárias ao tratamento farmacológico convencional: um novo horizonte - SANTOS NETO, Olival dos (2024)
Epilepsy is one of the most common neurological disorders in the world, there are records that have been in force since antiquity, it is characterized by abnormal and synchronous electrical discharges by brain neurons. With the advancement of science, several drugs were produced with the intention of obtaining control of the disease, which was a major milestone for the treatment of epileptics. Although, there are still patients who resist pharmacological treatment, presenting with refractory epilepsy, this is quite harmful for individuals who live with the disease, as it causes great damage to their intellectual, cognitive and social development, in addition to preventing some work activities. or recreational activities can be carried out. Thus, the development of new therapies that seek to control abnormal discharges from the Central Nervous System (CNS) is of paramount importance. which, by acting on endocannabinoid receptors, proves to be quite effective in controlling. Thus, the current study seeks to carry out a systematic literature review, gathering information on the use of cannabinoids in the treatment of this neurological abnormality and showing such benefits of Cannabis.